Granulomatosis after autologous stem cell transplantation in nonHodgkin lymphoma – experience of single institution and a review of literature - Boltezar, Lucka (Radiol Oncol, 2016)
BACKGROUND: Sarcoidosis before and after treatment of malignancy is an important differential diagnosis that has to be distinguished from lymphoma. PATIENTS AND METHODS: Hodgkin lymphoma, diffuse large B-cell lymphoma and aggressive follicular lymphoma are being staged and treatment effect is evaluated with PET-CT. We report three cases of aggressive lymphoma after high dose therapy and autologous stem cell transplantation with positive lymph nodes on PET-CT, which were histologically diagnosed as sarcoidosis/granulomatosis. In the literature, we found that false positive lymph nodes were more common after allogeneic than after autologous transplantation. CONCLUSIONS: Post-treatment PET-CT positive lymph nodes should always be examined histologically prior to any further treatment decision to avoid unnecessary toxic procedures.